The Impact Of Competitive Advantage On The Growth Of International Marketing: An Applied Study On The Karbala International Real Estate Investment Group And The Fardous Karbala International Real Estate Investment Company - Mayasah Nadhim Azeez Mohammed (Peerian Journals Publishing, 2025)
The aim of the research is to try to define the concept of competitive advantage and its types, to learn about the reality of international marketing, while revealing the extent of the existence of international marketing strategies in the companies of the study sample, in addition to arriving at global standards that express competitive advantage in the companies of the study sample, and also to identify the impact of competitive advantage. In the growth of international marketing. The research used a simple random sampling method to select the study sample, which was represented by workers at Karbala International Group for Real Estate Investments and Firdaus Karbala International Real Estate Investments Company, and its size reached 120 workers. The results of the study showed the existence of a formal strategy for international marketing in the companies under study. The research showed that the international standards that express the competitive advantage in the companies sampled by the study are represented by the effectiveness of international marketing. The goals of the effectiveness of international marketing were to obtain a distinguished position in the international market. The most important international marketing strategies that The study sample companies achieve competitive advantage through product strategy. The research indicated that the impact of competitive advantage on the growth of international marketing is achieving market power. The research recommended the need to expand training and development programs to develop employees, increase awareness of the importance of competitive advantage in the growth of international marketing, increase the use of modern computers and their applications to develop the company’s operations and improve the services provided to customers, and pay attention to developing modern strategies that contribute to expanding the scope of the company’s work in the international market.
Keywords: Competitive advantage; international marketing; Competitive Environment